Pengaruh Variasi Komposisi Terhadap Karakteristik Briket Campuran Sekam Padi Dan Kulit Jambu Mete - Manisi, La; Kadir, Kadir; Kadir, Abd . (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2019)
Rice husks and cashew nuts have an economical value of where can be transformed into an energy form one of them is briquette. This research aims to determine the influence of pressure composition on thermal characteristics of rice husk charcoal briquettes and cashew skin. In this study, the composition of the tested is briquette with a ratio of the raw material percentage of rice husk 30 % cashew skin 70 %, rice husk 50 % cashew skin 50 % and rice husk 70 % cashew bark 30%. The manufacture of briquette was performed pressure 50 kgf/cm2, 100 kgf/cm2, 150 kgf/cm2. The thermal testing of briquettes is carried out in a cylinder combustion furnace designed for natural airflow. In combustion testing used three briquettes for each composition. During the combustion, observations of the mass decline and increase in the fuel temperature increased by 1 minute using digital scales and K-Type Thermocouple. The results showed that the composition of mixing 30% rice husk: 70% cashew skin has the highest combustion temperature increase and the rate of decline in mass and long combustion at 50 kgf/cm2 pressure that the decline in the speed of the most rapid combustion of each minute is on the mixing briquette that has a composition of 30 % rice husk and 70 % cashew skin.Keywords: briquette, rice husk, and cashew skin